Complete mitochondrial genome analysis of Distolasterias nipon (Echinodermata, Asteroidea, Forcipulatida). Issue 2 (3rd July 2018) - Lee, Taekjun; Shin, Sook
Abstract: In this study, we determined the complete mitochondrial genome sequences of Distolasterias nipon belonging to the class Asteroidea in the phylum Echinodermata. The complete mitogenome of D. nipon was 16, 193 bp in length and consisted of 13 protein-coding genes (PCGs), 22 tRNAs, and 2 rRNAs. The orders of PCGs and rRNAs were identical to those of the eight recorded mitogenomes of asteroids. The phylogenetic tree determined by the maximum likelihood method revealed that D. nipon was clearly grouped with Aphelasterias japonica and Asterias amurensis, which belong to the family Asteriidae.